Analisis Pengembangan UMKM Olahan Tahu di Desa Mojowetan Banjarejo-Blora - Pardan; Kistanti, Nurjannah Rahayu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are an important pillar in supporting the national economy, especially at the rural level. This study aims to analyze the supporting factors, obstacles, and development strategies of tofu MSMEs in Mojowetan Village, Banjarejo District, Blora Regency, Central Java. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation of 15 MSMEs that have been operating for more than two years. SWOT analysis was used to identify strengths, weaknesses, opportunities, and threats in tofu production. The results show that the main strengths of Mojowetan tofu MSMEs lie in high product quality, rich nutritional value, and environmentally friendly waste utilization. However, weaknesses are still found in limited production equipment, fluctuations in raw material prices, and dependence on imported soybeans. Development opportunities include digital markets, product and packaging innovation, and support from the government and educational institutions. Meanwhile, threats faced include intense market competition and low digital literacy. A collaborative strategy is needed between MSMEs, the government, and other stakeholders in modernizing tools, strengthening human resource capacity, and developing digital marketing to create competitive and sustainable MSMEs.